NiOx Nanocrystals with Tunable Size and Energy Levels for Efficient and UV Stable Perovskite Solar Cells. (12th May 2022) - Cui, Xiaxia; Jin, Junjun; Zou, Junjie; Tang, Qiang; Ai, Yuan; Zhang, Xiang; Wang, Zhen; Zhou, Yuan; Zhu, Zhenkun; Tang, Guanqi; Cao, Qiang; Liu, Sheng; et al.
Abstract: Solution‐processed nickel oxide nanocrystals (NiOx NCs) ink can be facilely applied to deposit NiOx thin films as the hole transport layer (HTL) for perovskite solar cells (PSCs). Both the efficiency and stability of the corresponding PSCs depend significantly on the size and the energy levels of the as‐synthesized NiOx NCs; however, previous studies have shown that these two aspects can be hardly controlled synchronously to maximize the device performance. Herein, a novel synthesis of highly dispersed NiOx NCs is demonstrated by employing tetraalkylammonium hydroxides (TAAOHs, alkyl = methyl, ethyl, propyl, butyl) as precipitating bases, where the varied alkyl chain lengths of TAAOHs enable the size control of the NiOx NCs and the subsequent altering of their Ni 3+ contents, leading to tunable energy levels of the NiOx thin films. With the longest butyl chain, the smallest crystal size and the optimal energy level alignment at the NiOx /perovskite interface are achieved. After further passivating the detrimental Ni 3+ species on the surface of NiOx HTL, a remarkable power conversion efficiency (PCE) approaching 23% is obtained, which is one of the highest PCEs reported for NiOx ‐based inverted PSCs. Furthermore, the unencapsulated device exhibits excellent ultraviolet stability, which maintains ≈ 87% of its PCE after 200 h exposure. Abstract : Highly dispersed NiOx nanocrystals with tunable size and energy levels have been successfully synthesized and applied as hole transport layer for perovskite solar cells. Power conversion efficiency approaching 23% is achieved, together with excellent device stability under ultraviolet irradiance.